Pengaruh Bahan Ajar Keterampilan Berbicara Terhadap Kesantunan Berbahasa Mahasiswa Universitas Negeri Makassar Berdasarkan Perspektif Latar Budaya Mahasiswa - Muhammad Saleh; Salam Salam; Sakinah Fitri (Seminar Nasional LP2M UNM, 2022)
Abstract. Speaking skills and cultural/ethnic background of students allegedly affect language politeness in daily communication. This research aims to determine the effect of speaking skills teaching materials on improving the language politeness of Makassar State University students and the influence of students' cultural/ethnic background on their language politeness. This research uses a pre-experimental method. The instrument used in this research was a test, namely pretest and posttest. The results showed that the application of the model of speaking skills teaching materials can improve language politeness. The results of the second research showed that students with Bugis cultural/ethnic backgrounds had a greater impact on speaking politeness than students with Makassar cultural/ethnic backgrounds, especially students of Indonesian Language and Literature Education, Faculty of Language and Letters, State University of Makassar. Keywords: Teaching materials, speaking skills, language politeness, cultural